2002
DOI: 10.2337/diabetes.51.2007.s19
|View full text |Cite
|
Sign up to set email alerts
|

Fast and cAMP-Sensitive Mode of Ca2+-Dependent Exocytosis in Pancreatic β-Cells

Abstract: The fast component (mode 1) of Ca 2؉ -dependent exocytosis in pancreatic ␤-cells, unlike that in adrenal chromaffin cells, is regulated by cytosolic ATP in a concentration-dependent manner. This action of ATP is apparent within 3 min and does not require ATP hydrolysis; rather, it requires the production of cAMP by adenylate cyclase. Moreover, the effect of cAMP is ATP dependent, as revealed by the observation that the fast component of exocytosis is facilitated by ATP, even in the presence of a saturating con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 52 publications
4
32
0
Order By: Relevance
“…Interestingly, Hoppa et al did not observe a significant increase in primary exocytosis, shown in other reports to occur in response to GLP-1 potentiation [7,8]. In addition, granule-granule fusion kinetics varied according to the stimulating compound used, with GLP-1-stimulated release largely the result of sequential fusion [7,8] and carbacholstimulated release largely produced by multivesicular fusion [16].…”
Section: -Dmentioning
confidence: 87%
See 2 more Smart Citations
“…Interestingly, Hoppa et al did not observe a significant increase in primary exocytosis, shown in other reports to occur in response to GLP-1 potentiation [7,8]. In addition, granule-granule fusion kinetics varied according to the stimulating compound used, with GLP-1-stimulated release largely the result of sequential fusion [7,8] and carbacholstimulated release largely produced by multivesicular fusion [16].…”
Section: -Dmentioning
confidence: 87%
“…In addition, granule-granule fusion kinetics varied according to the stimulating compound used, with GLP-1-stimulated release largely the result of sequential fusion [7,8] and carbacholstimulated release largely produced by multivesicular fusion [16]. This would suggest that downstream exocytotic fusion molecules acted upon by carbachol-evoked calcium (and PKC) signalling may be distinct from the exocytotic molecules coupled to GLP-1-evoked cAMP/PKA signalling.…”
Section: -Dmentioning
confidence: 96%
See 1 more Smart Citation
“…By contrast Takahashi and colleagues have presented experimental evidence for the importance of PKA in fast glucose-induced exocytosis (Kasai et al, 2002;Takahashi et al, 1999). The model they have developed is a rapid and reversible post-priming step in which ATP acts independently of its effects on [Ca 2+ ] or the K ATP channels but requires PKA.…”
Section: Pka-dependent Versus Pka-independent Effects On Insulin Exocmentioning
confidence: 99%
“…Basal levels of cAMP (and presumably PKA) were sufficient to prime the β cell for this initial burst of vesicle release as FSK, even the presence of high ATP concentrations, did not augment insulin release whereas low concentrations did so. However, as Takahashi and colleagues point out, it is still not possible to rule out that a component of this Ca 2+ -dependent fast exocytosis could be dependent on another cAMP sensor such as Epac (Kasai et al, 2002).…”
Section: Pka-dependent Versus Pka-independent Effects On Insulin Exocmentioning
confidence: 99%